CPU socket
The CPU socket utilizes a liquid crystal polyester resin composition with specific structural units and inorganic fillers to address crack resistance and filling issues at narrow pitch intervals, resulting in a robust and reliable product.
Patent Information
- Application Number
- JP2024153916
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2024-04-18
- Filing Date
- 2024-09-06
- Publication Date
- 2025-05-02
AI Technical Summary
Existing CPU sockets face challenges with crack resistance, defects, and burrs due to narrow pitch intervals and increased injection molding temperatures and speeds, which affect the filling properties and strength of the weld portions.
A CPU socket formed from a liquid crystal polyester resin composition containing specific structural units and 60 to 200 parts by weight of inorganic filler per 100 parts by weight of resin, which includes fibrous and plate-like fillers to enhance filling properties and reduce cracking.
The solution provides a CPU socket with excellent crack resistance, reduced defects and burrs, and improved filling properties even at narrow pitch intervals, ensuring the strength and reliability of the lattice structure.
Smart Images

Figure 2025070972000012 
Figure 2025070972000013 
Figure 2025070972000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a CPU socket, and more particularly to a CPU socket obtained by using a liquid crystal polyester resin composition. [Background technology]
[0002] Liquid crystal polyester resins have excellent heat resistance, fluidity, and dimensional stability, and are therefore used in electrical and electronic components that require these properties. In particular, with the increasing performance of devices in recent years, there is an increasing need for molded products with thin walls and complex shapes, such as CPU (central processing unit) sockets.
[0003] A CPU socket is a connection terminal for an IC chip provided on a main board (motherboard) inside a computer, and the shape of the CPU socket is becoming more complex in response to the increasingly complex shapes of CPUs. As materials for conventional planar connectors such as CPU sockets, planar connectors have been proposed that are molded from composite resin compositions containing a plate-like filler such as a liquid crystal polymer having a specific structure, glass fiber, and talc (e.g., Patent Documents 1 and 2), or from a liquid crystal polyester composition containing a fibrous filler and a plate-like filler having a specific number-average aspect ratio (e.g., Patent Document 3), and have excellent moldability, low warpage, and crack resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO 2014 / 50370 [Patent Document 2] JP 2012-214652 A [Patent Document 3] JP 2012-193343 A Summary of the Invention [Problem to be solved by the invention]
[0005] In recent years, CPU sockets have become narrower in pitch due to the increased number of pins on CPUs, so the pitch interval of the lattice parts in the lattice structure is narrower and the width of the resin parts of the lattice parts that make up the lattice structure is also narrower, so there is a demand for a material that has excellent filling properties for filling the lattice structure and suppresses the occurrence of cracks from the welds of the lattice parts that are formed in large numbers. In addition, when molding a CPU socket with a narrower pitch as described above, when filling from the outer frame part, which is thick, to the lattice parts, which are thinner, a higher pressure is applied than before, so burrs (a phenomenon in which resin overflows from the gaps between the mating surfaces of the mold) are likely to occur, and a material that suppresses burrs is required.
[0006] Furthermore, fine-pitch CPU sockets are manufactured by injection molding of liquid crystal polyester resin, and in order to fully fill the thin grid area, they are often manufactured under conditions of high injection molding temperature and injection speed. In this case, the liquid crystal polyester resin fills the welds of the grid area before the glass fiber and other fillers, which reduces the reinforcing effect of the welds, making them more susceptible to cracking.
[0007] However, in the inventions shown in Patent Documents 1 to 3, in addition to the resin composition lacking in thin-wall fluidity, there is a lot of outgassing during molding, so there is a large variation in filling for each molded product, and the lattice structure with a narrow pitch cannot be completely filled, resulting in defective molded products and prone to burrs. Furthermore, there was a problem that the strength of the welds formed in the lattice structure was insufficient, especially under conditions of high injection molding temperature and injection speed, and cracks were generated.
[0008] The object of the present invention is to provide a CPU socket with excellent crack resistance, which has few defects and burrs due to little filling variation between molded products even with narrow pitch intervals, and is less susceptible to cracks in the lattice structure after molding. [Means for solving the problem]
[0009] The present inventors have conducted extensive research to solve the above problems, and have found that a liquid crystal polyester resin composition containing a liquid crystal polyester resin having a specific structural unit and a predetermined amount of inorganic filler can provide a CPU socket that can solve the above problems, and have arrived at the present invention. That is, the present invention has the following configuration.
[0010] (1) A CPU socket formed from a liquid crystal polyester resin composition containing 60 to 200 parts by weight of an inorganic filler (B) per 100 parts by weight of a liquid crystal polyester resin (A) which is a liquid crystal polyester resin containing at least the following structural units (I) to (V) and which satisfies the following formulas (a) to (d): 25≦[I]≦75 (a) 1≦[II]≦20 (b) 2≦[III]+[IV]≦35 (c) 2≦[V]≦35 (d) ([I] to [V] indicate the contents (mol %) of the following structural units (I) to (V) relative to 100 mol % of all structural units in the liquid crystal polyester resin.)
[0011] [ka]
[0012] (2) The CPU socket according to (1), wherein the inorganic filler (B) contains at least a fibrous filler having an average fiber length of 1 to 300 μm, and the content of the fibrous filler is 65 to 100% by weight relative to 100% by weight of the inorganic filler (B). (3) A CPU socket as described in (2), in which, with respect to the fibrous filler, fibrous fillers having a fiber length of 100 μm or more account for 0.1% or more and less than 30% of the total fibrous filler, in terms of the number of fibers. (4) A CPU socket according to any one of (1) to (3), wherein the inorganic filler (B) contains at least a plate-like filler, and the content of the plate-like filler is 35% by weight or less relative to 100% by weight of the inorganic filler (B). (5) The CPU socket according to any one of (1) to (4), wherein the liquid crystal polyester resin (A) further contains the following structural unit (VI) and is a liquid crystal polyester resin that satisfies the following formula (e): 0.05≦[VI]≦10 (e)
[0013] [ka]
[0014] (6) A CPU socket according to any one of (1) to (5), in which the minimum width of the resin portion of the lattice portion that constitutes the lattice structure is 0.2 mm or less. Effect of the Invention
[0015] The CPU socket of the present invention has few defects or burrs even with a narrow pitch, and has excellent crack resistance that makes it difficult for the lattice structure to crack after molding. Such a CPU socket is particularly suitable for use in small electrical and electronic components. [Brief description of the drawings]
[0016] [Figure 1] 1 is a diagram showing a plan view of a CPU socket molded in an embodiment, in which the unit is mm. [Diagram 2] This is a detail of part A in Figure 1. The unit in the figure is mm. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below.
[0018] <Liquid crystal polyester resin (A)> The liquid crystal polyester resin is a polyester that forms an anisotropic molten phase. Examples of such polyester resins include polyesters composed of structural units selected from oxycarbonyl units, dioxy units, dicarbonyl units, etc., which will be described later, so as to form an anisotropic molten phase. Next, the structural units constituting the liquid crystal polyester resin will be described.
[0019] The liquid crystal polyester resin (A) used in the present invention contains, as an oxycarbonyl unit, 25 to 75 mol% of the following structural unit (I) derived from p-hydroxybenzoic acid relative to 100 mol% of all structural units of the liquid crystal polyester resin (A). If it is less than 25 mol% or more than 75 mol%, gas during processing increases, and fluidity and strength deteriorate, resulting in more defects and burrs in the CPU socket and worsening crack resistance. From the viewpoint of obtaining a CPU socket with fewer defects and burrs and excellent crack resistance, it is preferably 30 mol% or more, more preferably 40 mol% or more, and even more preferably 45 mol% or more. On the other hand, it is preferably 65 mol% or less, more preferably 60 mol% or less, and even more preferably 55 mol% or less.
[0020] [ka]
[0021] The liquid crystal polyester resin (A) used in the present invention is characterized in that it contains, as an oxycarbonyl unit, the following structural unit (II) derived from 6-hydroxy-2-naphthoic acid, in an amount of 1 to 20 mol % relative to 100 mol % of all structural units of the liquid crystal polyester resin (A). The structural unit (II) has a naphthalene ring structure, and has a different molecular chain length from the structural unit (I) having a benzene ring, so that the molecular chain of the liquid crystal polyester resin can be suppressed from being tightly packed while maintaining liquid crystallinity. From the viewpoint of improving thin-wall fluidity, reducing defects and burrs, and obtaining a CPU socket with excellent crack resistance, the amount is preferably 2 mol % or more, more preferably 3 mol % or more. On the other hand, the amount is preferably 14 mol % or less, more preferably 8 mol % or less. Note that when the structural unit (II) is less than 1 mol %, burrs increase and thin-wall fluidity deteriorates, and when it is more than 20 mol %, strength deteriorates, resulting in more defects in the CPU socket and worsening crack resistance.
[0022] [ka]
[0023] In the liquid crystal polyester resin (A) used in the present invention, from the viewpoint of obtaining a CPU socket having few defects and burrs and excellent crack resistance, the molar ratio ([I] / [II]) of the contents of the structural units (I) and (II) is preferably 3 or more, more preferably 5 or more, and even more preferably 7 or more. On the other hand, it is preferably 20 or less, more preferably 18 or less, and even more preferably 16 or less.
[0024] The liquid crystal polyester resin (A) used in the present invention is characterized in that it contains, as dioxy units, 2 to 35 mol% in total of the structural unit (III) derived from 4,4'-dihydroxybiphenyl and the following structural unit (IV) derived from hydroquinone, relative to 100 mol% of all structural units of the liquid crystal polyester resin (A). By using the structural unit (III) and the structural unit (IV) having different molecular chain lengths as dioxy units in combination, packing of the liquid crystal polyester resin can be suppressed, and thin wall fluidity is improved. In addition, by using dioxy units having different reactivity in combination, the end group of the liquid crystal polyester resin is controlled, and gas during processing is reduced. From the viewpoint of obtaining a CPU socket with fewer defects and burrs and excellent crack resistance, the total amount of the structural units (III) and (IV) is preferably 7 mol% or more, more preferably 12 mol% or more, and even more preferably 17 mol% or more. On the other hand, it is preferably 30 mol% or less, and even more preferably 25 mol% or less.
[0025] [ka]
[0026] From the viewpoint of obtaining a CPU socket with few defects and burrs and excellent crack resistance, the structural unit (III) is preferably 1 mol% or more, more preferably 4 mol% or more, and even more preferably 8 mol% or more, based on 100 mol% of all structural units of the liquid crystal polyester resin (A), while it is preferably 25 mol% or less, more preferably 20 mol% or less, and even more preferably 15 mol% or less.
[0027] From the viewpoint of obtaining a CPU socket with few defects and burrs and excellent crack resistance, the structural unit (IV) is preferably 1 mol% or more, more preferably 6 mol% or more, and even more preferably 11 mol% or more, based on 100 mol% of all structural units of the liquid crystal polyester resin (A), while it is preferably 30 mol% or less, more preferably 25 mol% or less, and even more preferably 20 mol% or less.
[0028] In order to obtain a CPU socket having few defects and burrs and excellent crack resistance, the liquid crystal polyester resin used in the present invention preferably has a molar ratio ([III] / [IV]) of the contents of the structural units (III) and (IV) larger than 0, more preferably 0.3 or more, and even more preferably 0.6 or more. On the other hand, it is preferably smaller than 1.5, more preferably 1.2 or less, and even more preferably 1.0 or less.
[0029] The liquid crystal polyester resin (A) used in the present invention contains 2 to 35 mol% of structural units (V) derived from terephthalic acid as dicarbonyl units relative to 100 mol% of all structural units of the liquid crystal polyester resin (A). If it is less than 2 mol% or more than 35 mol%, gas during processing increases, and fluidity and strength deteriorate, resulting in more defects and burrs in the CPU socket and worsening crack resistance. From the viewpoint of obtaining a CPU socket with fewer defects and burrs and excellent crack resistance, it is preferably 7 mol% or more, more preferably 12 mol% or more, and even more preferably 17 mol% or more. On the other hand, it is preferably 30 mol% or less, more preferably 25 mol% or less.
[0030] [ka]
[0031] The liquid crystal polyester resin (A) used in the present invention preferably contains 0.01 to 10 mol% of the structural unit (VI) derived from isophthalic acid as a dicarbonyl unit relative to 100 mol% of all structural units of the liquid crystal polyester resin (A). Since the structural unit (VI) has a significantly curved structure compared to other monomers, it is possible to suppress packing of the liquid crystal polyester resin and improve thin-wall fluidity. From the viewpoint of obtaining a CPU socket with fewer defects and burrs and excellent crack resistance, it is preferably 0.05 mol% or more, more preferably 0.1 mol% or more. On the other hand, it is preferably 8 mol% or less, more preferably 6 mol% or less, and even more preferably 4 mol% or less.
[0032] [ka]
[0033] In the liquid crystal polyester resin used in the present invention, from the viewpoint of obtaining a CPU socket having few defects and burrs and excellent crack resistance, the molar ratio ([VI] / [II]) of the contents of the structural units (VI) and (II) is preferably less than 1, and is preferably 0.9 or less. On the other hand, the lower limit of [VI] / [II] is not particularly limited, and may be 0.005 or more. From the viewpoint of obtaining a CPU socket having few defects and excellent crack resistance, [VI] / [II] is preferably 0.01 or more, and more preferably 0.05 or more.
[0034] In addition to the above structural units, structural units derived from ethylene glycol, p-aminobenzoic acid, p-aminophenol, etc. may be contained within the range that does not impair the liquid crystallinity or other characteristics.
[0035] The monomers serving as raw materials for forming each of the structural units described above are not particularly limited as long as they have a structure capable of forming each of the structural units. In addition, acylation products of the hydroxyl groups of such monomers, esterification products of the carboxyl groups, acid halides, acid anhydrides and other carboxylic acid derivatives may be used.
[0036] The method for calculating the content of each structural unit in the liquid crystal polyester resin is as follows. First, the liquid crystal polyester resin is pulverized, and then tetramethylammonium hydroxide is added. The content can be determined by pyrolysis GC / MS measurement using a Shimadzu GCMS-QP5050A. The content of structural units that are not detected or are below the detection limit is calculated as 0 mol%.
[0037] The melting point (Tm) of the liquid crystal polyester resin (A) is preferably 280°C or higher, more preferably 300°C or higher, and even more preferably 320°C or higher, from the viewpoint of obtaining a CPU socket having excellent crack resistance due to excellent heat resistance. On the other hand, the melting point (Tm) of the liquid crystal polyester resin (A) is preferably 370°C or lower, more preferably 360°C or lower, and even more preferably 350°C or lower, from the viewpoint of obtaining a CPU socket having few defects and excellent crack resistance by not having a too high processing temperature and being less likely to generate gas during processing. The melting point (Tm) is measured by differential scanning calorimetry. Specifically, first, the liquid crystal polyester resin (A) is heated from room temperature at a temperature increase condition of 20°C / min to obtain an endothermic peak temperature (Tm 1 ) is observed. 1 ) and then the endothermic peak temperature (Tm 1 The polymer is then held at a temperature of +20°C for 5 minutes. The polymer is then cooled to room temperature at a temperature drop of 20°C / min. The polymer is then heated at a temperature rise of 20°C / min to obtain the endothermic peak temperature (Tm 2 The melting point (Tm) is the endothermic peak temperature (Tm 2 )
[0038] From the viewpoint of obtaining a CPU socket having excellent strength and therefore excellent crack resistance, the melt viscosity of the liquid crystal polyester resin is preferably 3 Pa·s or more, more preferably 4 Pa·s or more, and even more preferably 5 Pa·s or more. On the other hand, from the viewpoint of obtaining a CPU socket having excellent fluidity, which has few defects and burrs and has excellent crack resistance, the melt viscosity of the liquid crystal polyester resin is preferably 50 Pa·s or less, preferably 40 Pa·s or less, and even more preferably 30 Pa·s or less.
[0039] The melt viscosity is a value measured by a Koka type flow tester at a temperature of the melting point (Tm) of the liquid crystal polyester resin + 20° C. under the condition of a shear rate of 1000 / sec.
[0040] <Method for producing liquid crystal polyester resin (A)> The method for producing the liquid crystal polyester resin (A) used in the present invention is not particularly limited, and can be produced in accordance with a known polyester polycondensation method. Examples of known polyester polycondensation methods include the following, for example, liquid crystal polyester resin (A) consisting of a structural unit derived from p-hydroxybenzoic acid, a structural unit derived from 6-hydroxy-2-naphthoic acid, a structural unit derived from 4,4'-dihydroxybiphenyl, a structural unit derived from hydroquinone, and a structural unit derived from terephthalic acid and isophthalic acid.
[0041] (1) A method for producing a liquid crystal polyester resin (A) from p-acetoxybenzoic acid, 6-acetoxy-2-naphthoic acid, 4,4'-diacetoxybiphenyl, diacetoxybenzene, terephthalic acid, and isophthalic acid by a deacetic acid condensation polymerization reaction.
[0042] (2) A method for producing a liquid crystal polyester resin (A) by reacting p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 4,4'-dihydroxybiphenyl, hydroquinone, terephthalic acid, and isophthalic acid with acetic anhydride to acetylate the phenolic hydroxyl groups, followed by deacetylation polymerization.
[0043] (3) A method for producing a liquid crystal polyester resin (A) by a dephenolation polycondensation reaction of phenyl p-hydroxybenzoate, phenyl 6-hydroxy-2-naphthoate, 4,4'-dihydroxybiphenyl, hydroquinone, diphenyl terephthalate, and diphenyl isophthalate.
[0044] (4) A method in which a predetermined amount of diphenyl carbonate is reacted with aromatic carboxylic acids, such as p-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, terephthalic acid, and isophthalic acid, to form the phenyl esters, respectively, and then an aromatic dihydroxy compound, such as 4,4'-dihydroxybiphenyl or hydroquinone, is added to carry out a dephenolation polycondensation reaction to produce a liquid crystal polyester resin (A).
[0045] Among these, the method (2) of reacting p-hydroxybenzoic acid, 4,4'-dihydroxybiphenyl, hydroquinone, terephthalic acid, and isophthalic acid with acetic anhydride to acetylate the phenolic hydroxyl groups, followed by a deacetylase polycondensation reaction to produce the liquid crystal polyester resin (A) is preferably used because it is industrially excellent in controlling the terminal structure and the degree of polymerization of the liquid crystal polyester resin (A).
[0046] As a method for producing the liquid crystal polyester resin (A) used in the present invention, it is also possible to complete the polycondensation reaction by a solid-phase polymerization method. Examples of the treatment by the solid-phase polymerization method include the following method. First, the polymer or oligomer of the liquid crystal polyester resin (A) is pulverized by a pulverizer. The pulverized polymer or oligomer is heated under a nitrogen stream or reduced pressure to polycondense to a desired degree of polymerization, thereby completing the reaction. The heating can be performed for 1 to 50 hours at a temperature in the range of the melting point of the liquid crystal polyester resin (A) -50°C to the melting point -5°C (for example, 200 to 300°C).
[0047] <Inorganic filler (B)> The liquid crystal polyester resin composition used in the present invention is characterized by containing 60 to 200 parts by weight of inorganic filler (B) per 100 parts by weight of liquid crystal polyester resin (A). By increasing the content of inorganic filler (B) relatively, gas derived from liquid crystal polyester resin during melt processing can be further reduced, and excessive orientation of liquid crystal polyester resin during molding can be suppressed. As a result, a CPU socket having excellent filling properties and fewer defects in the lattice structure portion, improved strength of the weld portion, and excellent crack resistance can be obtained. 65 parts by weight or more is preferable, 70 parts by weight or more is more preferable, and 80 parts by weight or more is even more preferable. On the other hand, 180 parts by weight or less is preferable, and 160 parts by weight or less is more preferable. Note that, when the content of inorganic filler (B) is less than 60 parts by weight, gas derived from liquid crystal polyester resin during melt processing increases, and liquid crystal polyester resin is excessively oriented during molding, so that filling properties at corners of the lattice structure deteriorate, and when it is more than 200 parts by weight, thin-wall fluidity deteriorates, so that defects and burrs of the CPU socket increase and crack resistance deteriorates.
[0048] The inorganic filler (B) used in the present invention is not particularly limited, and examples thereof include fibrous, whisker-like, plate-like, powdery, and granular fillers. Specifically, examples of fibrous and whisker-like fillers include glass fibers, stainless steel fibers, metal fibers such as aluminum fibers and brass fibers, gypsum fibers, ceramic fibers, asbestos fibers, zirconia fibers, alumina fibers, silica fibers, titanium oxide fibers, silicon carbide fibers, rock wool, potassium titanate whiskers, barium titanate whiskers, aluminum borate whiskers, silicon nitride whiskers, and needle-like titanium oxide. Examples of plate-like fillers include mica, talc, kaolin, glass flakes, clay, molybdenum disulfide, and wollastonite. Examples of powdery and granular fillers include silica, glass beads, titanium oxide, zinc oxide, and calcium polyphosphate. The above-mentioned fillers used in the present invention may have their surfaces treated with a known coupling agent (e.g., a silane-based coupling agent, a titanate-based coupling agent, etc.) or other surface treatment agent. The above-mentioned fillers used in the present invention may be used in combination of two or more kinds.
[0049] Among the above fillers, it is preferable to use a fibrous filler, since it can suppress the liquid crystal polyester resin from being excessively oriented during molding, and therefore the filling of the lattice structure is excellent, there are fewer defects, and the mechanical strength such as tensile strength and bending strength, heat resistance, and dimensional stability are excellent, so that a CPU socket with excellent crack resistance can be obtained. Among them, it is more preferable to use glass fiber. The type of glass fiber is not particularly limited as long as it is generally used for reinforcing resin, and examples thereof include chopped strands of long fiber type and short fiber type, milled fiber, and the like.
[0050] The fibrous filler used in the present invention preferably has an average fiber length in the liquid crystal polyester resin composition of 1 to 300 μm from the viewpoint of obtaining a CPU socket having excellent fluidity, few defects, and excellent crack resistance. The average fiber length is preferably 10 μm or more, more preferably 20 μm or more. On the other hand, in addition to the above-mentioned effects, from the viewpoint of excellent crack resistance, particularly under conditions of increased injection molding temperature and injection speed, the average fiber length is preferably 270 μm or less, more preferably 240 μm or less, even more preferably 150 μm or less, and particularly preferably 65 μm or less.
[0051] In the liquid crystal polyester resin composition used in the present invention, the fibrous filler having a fiber length of 100 μm or more is preferably less than 30% of the total fibrous filler based on the number of fibers. In this way, in the case of a fibrous filler having a small proportion of long fibers, the flowability is excellent, so that the fibrous filler can be easily filled into narrow parts, and the reinforcing effect of the weld part is improved. From the above, a CPU socket having few defects and burrs and excellent crack resistance can be obtained, especially under conditions of increased injection molding temperature and injection speed. The proportion of the fibrous filler having a fiber length of 100 μm or more is preferably less than 27%, more preferably less than 24%, and even more preferably less than 20%. On the other hand, the presence of a moderate amount of fibrous filler with a fiber length of 100 μm or more improves the reinforcing effect of the weld section, reduces defects and burrs, and produces a CPU socket with excellent crack resistance, especially under conditions of increased injection molding temperature and injection speed. Therefore, it is preferable that the amount of fibrous filler with a fiber length of 100 μm or more be 0.1% or more of the total fibrous filler, and more preferably 0.5% or more.
[0052] Among glass fibers, milled fiber is preferably used because it is easy to control the average fiber length and fiber length distribution as described above, the liquid crystal polyester resin composition has excellent fluidity, and a CPU socket with few defects and excellent crack resistance can be obtained. If necessary, the average fiber length and fiber length distribution can be controlled by a sieve, or chopped strands can be used in combination to control the average fiber length and fiber length distribution.
[0053] The average fiber length of the fibrous filler and the proportion of fibrous fillers with a fiber length of 100 μm or more can be determined by the following method. 50 g of the liquid crystal polyester resin composition is heated in air at 550 ° C for 3 hours to remove the resin component, and the residue remaining as a non-combustible material is dispersed on a slide glass using liquid paraffin, and a stereomicroscope (Leica "M205C") is used to observe multiple images at a dispersed state and magnification (about 100 times) where about 100 to 200 fibrous fillers are observed in the observation image, and 1000 fibrous fillers are randomly selected using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to measure the fiber length, and the number average fiber length is calculated, which is the average fiber length of the fibrous filler. In addition, the number of fibrous fillers with a fiber length of 100 μm or more is determined, and the presence ratio (%) is calculated.
[0054] When the inorganic filler (B) used in the present invention contains a fibrous filler having an average fiber length in the above-mentioned preferred range, it is preferable to contain 65% by weight or more of the inorganic filler (B) 100% by weight, more preferably 70% by weight or more, even more preferably 80% by weight or more, and particularly preferably 90% by weight or more, from the viewpoint of obtaining a CPU socket having excellent crack resistance due to excellent filling property and fewer defects, and excellent mechanical strength. The upper limit is 100% by weight, but from the viewpoint of suppressing burrs, it is preferable to contain less than 100% by weight, more preferably 95% by weight or less, and even more preferably 90% by weight or less.
[0055] In addition, from the viewpoint of excellent thin-wall fluidity and suppression of burrs, it is preferable to use a plate-shaped filler. Plate-shaped fillers have better thin-wall fluidity than fibrous fillers, reduce the injection pressure during molding, and can increase the crystallinity of the liquid crystal polyester resin, so that the solidification speed can be controlled and burrs can be suppressed.
[0056] The plate-like filler referred to here means a filler having a ratio of average particle size to average thickness of 2 or more. The average particle size and average thickness can be determined by the following method. First, 3 g of the liquid crystal polyester resin composition is heated in air at 550°C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material is obtained. The average particle size is determined by weighing 100 mg of the resulting residue, dispersing it on a slide glass using liquid paraffin, and observing multiple images using a stereomicroscope (Leica "M205C") at a dispersion state and magnification (approximately 500 to 1000 times) where about 50 to 100 plate-like fillers are observed in the observation image, and randomly selecting 1000 plate-like fillers using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to measure the major axis of the plate-like fillers, and calculating the number average value. The average thickness was determined by observing the residue with a scanning electron microscope (SEM) ("JSM-6360LV" manufactured by JEOL Ltd.) at a magnification of 2000 times, measuring the thicknesses of 10 randomly selected plate-like fillers from the image, and calculating the number average value by adjusting the observation direction and angle.
[0057] When the inorganic filler (B) used in the present invention contains a plate-like filler, it is preferable to contain 5% by weight or more, more preferably 10% by weight or more, based on 100% by weight of the inorganic filler (B), from the viewpoint of excellent thin-wall flowability and suppression of burrs. On the other hand, from the viewpoint of obtaining a CPU socket with excellent crack resistance due to fewer defects and excellent mechanical strength, it is preferable to contain 35% by weight or less, more preferably 30% by weight or less.
[0058] The average particle size of the plate-like filler is preferably 1 μm or more, more preferably 5 μm or more, from the viewpoint of excellent thin-wall fluidity and suppressing burrs, and is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of excellent thin-wall fluidity and suppressing burrs. In addition, when a fibrous filler and a plate-like filler are used in combination as the inorganic filler (B), the ratio ((b-1) / (b-2)) of the average fiber length (b-1) of the fibrous filler in the liquid crystal polyester resin composition to the average particle size (b-2) of the plate-like filler is preferably 1 or more, more preferably 2 or more, from the viewpoint of obtaining a CPU socket having excellent mechanical strength and crack resistance, in addition to reducing defects and burrs. On the other hand, from the viewpoint of obtaining a CPU socket having excellent filling properties, reduced defects and burrs, and excellent crack resistance, it is preferably 10 or less, more preferably 7 or less.
[0059] As the plate-like filler, mica and talc are particularly preferred from the viewpoint of suppressing burrs.
[0060] The liquid crystal polyester resin composition used in the present invention may further contain conventional additives selected from antioxidants, heat stabilizers (e.g., hindered phenols, phosphites, thioethers, and their substitutes), ultraviolet absorbers (e.g., resorcinol, salicylate), color inhibitors such as phosphites and hypophosphites, lubricants and mold release agents (montanic acid and its metal salts, its esters, its half esters, stearyl alcohol, stearamide, and polyethylene wax), colorants including dyes or pigments, conductive agents or colorants such as carbon black, crystal nucleating agents, plasticizers, flame retardants (bromine-based flame retardants, phosphorus-based flame retardants, red phosphorus, silicone-based flame retardants, etc.), flame retardant assistants, and antistatic agents, within the scope of the present invention.
[0061] <Method of producing liquid crystal polyester resin composition> Methods for blending the inorganic filler (B) and other additives with the liquid crystal polyester resin (A) to prepare a liquid crystal polyester resin composition include, for example, a dry blend method in which the inorganic filler (B) and other solid additives are blended with the liquid crystal polyester resin (A), a solution blending method in which the inorganic filler (B) and other liquid additives are blended with the liquid crystal polyester resin (A), a method in which the inorganic filler (B) and other additives are added during polymerization of the liquid crystal polyester resin (A), and a method in which the inorganic filler (B) and other additives are melt-kneaded with the liquid crystal polyester resin (A), and among these, the melt-kneading method is preferred.
[0062] The melt kneading can be carried out by a known method, such as a Banbury mixer, a rubber roll machine, a kneader, a single-screw or twin-screw extruder, etc. Among them, a twin-screw extruder is preferable.
[0063] Examples of the kneading method include: 1) a method in which the liquid crystal polyester resin (A), the inorganic filler (B) and other additives are fed from a feeder at once and kneaded (lump-kneading method); 2) a method in which the liquid crystal polyester resin (A) and other additives are fed from a feeder and kneaded, and then the inorganic filler (B) is added from a side feeder and kneaded (side feed method); and 3) a method in which a liquid crystal polyester composition (master pellet) containing a high concentration of the liquid crystal polyester resin (A), the inorganic filler (B) and other additives is prepared, and then the master pellet is kneaded with the liquid crystal polyester resin (A) to a specified concentration (master pellet method). In addition, examples of the method of adding other additives include a lump-kneading method, a sequential addition method, and a method of adding a high concentration composition (master), and any method may be used.
[0064] <CPUソケット> The CPU socket of the present invention is formed from a liquid crystalline polyester resin composition containing 60 to 200 parts by weight of an inorganic filler (B) per 100 parts by weight of a liquid crystalline polyester resin (A) which contains at least the following structural units (I) to (V) and satisfies the following formulas (a) to (d): 25≦[I]≦75 (a) 1≦[II]≦20 (b) 2≦[III]+[IV]≦35 (c) 2≦[V]≦35···(d).
[0065] The inventors have found that such liquid crystal polyester resin (A) has excellent thin-wall flowability and, in particular, reduces gas during melt processing. Furthermore, by combining it with a relatively large content of inorganic filler (B), the gas derived from the liquid crystal polyester resin is further reduced, so that when continuously molded, the molded product has few defects and burrs due to gas generation and has excellent crack resistance, and is therefore suitable for CPU sockets having a lattice structure with a narrow pitch.
[0066] Specifically, a liquid crystal polyester resin composition having a weight loss rate of 0.21% by weight or less when kept at a temperature of the melting point of the liquid crystal polyester + 20°C for 60 minutes under a nitrogen gas atmosphere is particularly suitable for CPU sockets in terms of reducing gas during melt processing. The weight loss rate is preferably 0.20% by weight or less, more preferably 0.19% by weight or less. The lower limit is not particularly limited, and the lower the weight loss rate, the more preferable it is, but it may be, for example, 0.01% by weight or more.
[0067] The shape of the CPU socket is not particularly limited as long as it has a lattice structure inside the outer frame, and may have an opening of an appropriate size within the lattice structure.
[0068] A CPU socket in one embodiment will be described in detail. For example, the CPU socket shown in FIG. 1 and FIG. 2 is a plate-shaped molded product of length 39.85 mm × width 41.70 mm × height (thickness) 1.0 mm, molded by injection molding from three gate positions 1, and has a lattice structure 3 inside from positions 2.0 mm thick from the upper and lower ends of the outer frame portion 2. Also, a resin portion of 2 mm thick is provided in the center of the width 41.70 mm. The lattice structure 3 includes a lattice portion consisting of a resin portion and a pin insertion hole 4, and a lattice portion with a pitch interval of 1.2 mm and a resin portion of 0.15 mm is formed inside the outer frame portion 2, and further, an opening is provided in the center of the lattice structure 3 in an inner frame portion of 1.2 mm thick. A lattice portion of 15 columns × 2 × 30 rows is formed, but the number of lattice portions is 780 because of the opening.
[0069] The lattice structure referred to here is a structure in which a number of through holes (pin insertion holes) are formed at a predetermined interval in the vertical and horizontal directions by a number of resin parts extending vertically and horizontally on the plate surface of the CPU socket. The shape of the through holes is rectangular in Figures 1 and 2, but is not particularly limited and may be round, etc.
[0070] The lattice portion here refers to a portion including one through hole and a resin portion between the through hole and the adjacent through hole. The number of the lattice portions can be selected as necessary, and can be, for example, 500 to 10,000.
[0071] The pitch here is the sum of the width of the resin part of the lattice part constituting the lattice structure and the width of the through hole. The width of the through hole is the longest straight line distance between adjacent resin parts. The pitch can be selected as needed, but from the viewpoint of manufacturing a high-performance CPU socket with many pins and space saving, it is preferably 1.5 mm or less, more preferably 1.3 mm or less, and even more preferably 1.2 mm or less. On the other hand, from the viewpoint of excellent filling ability, few defects, and excellent crack resistance, it is preferably 0.6 mm or more, more preferably 0.7 mm or more. It is even more preferable to be 0.8 mm or more. In addition, the width of the resin part of the lattice part constituting the lattice structure can be selected as needed, but from the viewpoint of manufacturing a high-performance CPU socket with many pins and space saving, it is preferably 0.20 mm, more preferably 0.18 mm or less, and even more preferably 0.16 mm or less. On the other hand, from the viewpoint of excellent filling ability, few defects, and excellent crack resistance, it is preferably 0.08 mm or more, more preferably 0.10 mm or more, and even more preferably 0.12 mm or more. By using the liquid crystal polyester resin composition used in the present invention, it is possible to obtain a CPU socket that has few defects and burrs and has excellent crack resistance even if it has such a very thin portion.
[0072] The method of molding the liquid crystal polyester resin composition used in the present invention into a CPU socket includes molding methods such as ordinary injection molding, extrusion molding, and press molding, and can be processed into a CPU socket having excellent surface appearance (color tone), mechanical properties, and heat resistance. In particular, injection molding is preferable from the viewpoint of processability. When injection molding is performed, the cylinder temperature during injection molding is preferably 370°C or less, more preferably 360°C or less, from the viewpoint of suppressing deterioration of the liquid crystal polyester resin composition and reducing gas, thereby obtaining a CPU socket with fewer defects and burrs and excellent crack resistance.
[0073] The mold temperature is preferably 70° C. or higher from the viewpoint of the fluidity of the liquid crystal polyester resin composition, and is preferably 130° C. or lower from the viewpoint of suppressing defects such as burrs. EXAMPLES
[0074] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The liquid crystal polyester resin (A) described in the production examples was evaluated in the following items (1) to (3), and the results are shown in Table 1.
[0075] [Table 1]
[0076] (1) Composition analysis of liquid crystal polyester resin (A) To 0.1 mg of the ground liquid crystal polyester resin, 2 μL of a 25% methanol solution of tetramethylammonium hydroxide was added, and pyrolysis GC / MS measurement was performed using a Shimadzu GCMS-QP5050A to determine the composition ratio of each component in the liquid crystal polyester resin.
[0077] (2) Melting point (Tm) measurement of liquid crystal polyester resin (A) The endothermic peak temperature (Tm 1 ), Tm 1 After keeping the temperature at +20°C for 5 minutes, the sample was cooled to room temperature at a temperature drop rate of 20°C / min, and then heated again at a temperature rise rate of 20°C / min. The endothermic peak temperature observed when the sample was heated was taken as the melting point (Tm).
[0078] (3) Melt Viscosity of Liquid Crystal Polyester Resin (A) The melt viscosity of the liquid crystal polyester resin was measured at Tm+20° C. and a shear rate of 1000 / s using a high-performance flow tester CFT-500D (orifice 0.5φ×10 mm) (manufactured by Shimadzu Corporation).
[0079] [Production Example 1] In a 5L reaction vessel equipped with an agitator and a distillation tube, 808 parts by weight of p-hydroxybenzoic acid (HBA), 88 parts by weight of 6-hydroxy-2-naphthoic acid (HNA), 229 parts by weight of 4,4'-dihydroxybiphenyl (DHB), 161 parts by weight of hydroquinone (HQ), 428 parts by weight of terephthalic acid (TPA), 19 parts by weight of isophthalic acid (IPA) and 1278 parts by weight of acetic anhydride (1.07 equivalents of phenolic hydroxyl groups in total) were charged as monomers, and reacted at 145°C for 120 minutes while stirring under a nitrogen gas atmosphere, and then the temperature was raised from 145°C to 360°C over 4 hours. Thereafter, the polymerization temperature was maintained at 360°C, the pressure was reduced to 1.0 mmHg (133 Pa) over 1.0 hour, and the reaction was continued until the polymerization was completed when a predetermined stirring torque was reached. Next, the polymer was discharged in the form of strands through a die having one circular discharge port with a diameter of 6 mm, and pelletized with a cutter to obtain a liquid crystal polyester resin (A-1).
[0080] [Production Example 2] A liquid crystal polyester resin (A-2) was obtained in the same manner as in Example 1, except that the monomer charges were changed to 582 parts by weight of HBA, 88 parts by weight of HNA, 305 parts by weight of DHB, 206 parts by weight of HQ, and 583 parts by weight of TPA.
[0081] [Production Example 3] A liquid crystal polyester resin (A'-3) was obtained in the same manner as in Example 1, except that the monomer charges were changed to 808 parts by weight of HBA, 88 parts by weight of HNA, 501 parts by weight of DHB, 408 parts by weight of TPA, and 39 parts by weight of IPA.
[0082] [Production Example 4] A liquid crystal polyester resin (A'-4) was obtained in the same manner as in Example 1, except that the monomer charges were changed to 970 parts by weight of HBA, 436 parts by weight of DHB, 292 parts by weight of TPA, and 97 parts by weight of IPA.
[0083] Inorganic filler (B) Fibrous Filler (B-1) Glass fiber: EFH75-01 (milled fiber manufactured by Central Glass Fiber Co., Ltd., average fiber length 75 μm) (B-2) Glass fiber: ECS03T-747H (manufactured by Nippon Electric Glass Co., Ltd., fiber length (cut length) 3 mm) Plate-shaped filler (B-3) Talc: RL217 (manufactured by Fuji Talc Industrial Co., Ltd., median diameter 20 μm) (B-4) Mica: AB-25S (manufactured by Yamaguchi Mica Co., Ltd., median diameter 24 μm) (B-5) The glass fibers of (B-1) were sieved using a 120 mesh sieve to have the average fiber length described below, and the glass fibers that passed through the sieve were used. (Average fiber length before blending: 48 μm)
[0084] [Examples 1 to 10, Comparative Examples 1 to 3] The liquid crystal polyester resin (A) and inorganic filler (B) obtained in each production example were introduced into a twin-screw extruder (TEX-30α, manufactured by Japan Steel Works) with a screw diameter of 30 mm and L / D of 35 and equipped with a co-rotating vent, in the amounts shown in Table 2. The liquid crystal polyester resin (A) was added from the bottom of the twin-screw extruder, and the inorganic filler (B) was added by installing a side feeder between the bottom and vent sections. The cylinder temperature was set to the melting point of the liquid crystal polyester resin (A) + 10°C, and melt kneading was performed, discharged in the form of a strand, solidified through a cooling bath, and then pelletized with a strand cutter and used for the evaluations of (4) to (7).
[0085] (4) Gas Generation Amount of Liquid Crystal Polyester Resin Composition The pellets obtained in each Example and Comparative Example were dried with hot air at 150°C for 3 hours using a hot air dryer, and then 20 mg of an arbitrary portion was cut out and held at a temperature of the melting point of the liquid crystal polyester + 20°C for 60 minutes in a nitrogen gas atmosphere using a thermogravimetric analyzer (TGA), and the weight loss rate (wt%) was determined as the amount of gas generated. The smaller the amount of gas generated, the less gas was generated during melt processing, which was considered to be excellent.
[0086] (5) Average fiber length of glass fibers (b-1), percentage of fibrous fillers with fiber length of 100 μm or more 50g of the liquid crystal polyester resin composition was heated in air at 550°C for 3 hours to remove the resin component, and the residue remaining as a non-combustible material was dispersed on a slide glass using liquid paraffin, and multiple pieces were observed using a stereomicroscope (Leica "M205C") at a dispersion state and magnification (about 100 times) where about 100 to 200 glass fibers were observed in the observation image, and 1000 fibrous fillers were randomly selected using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to measure the fiber length, and the number average fiber length was calculated, which was the average fiber length of the glass fibers. In addition, the number of fibrous fillers with a fiber length of 100 μm or more was determined, and their presence ratio (%) was calculated.
[0087] (6) Average particle size of plate-like filler (b-2) 3 g of the liquid crystal polyester resin composition obtained in Examples 6 to 8 was heated in air at 550°C for 3 hours to remove the liquid crystal polyester resin (A) component, and the residue remaining as a non-combustible material was dispersed on a slide glass using liquid paraffin, and multiple images were observed using a stereomicroscope (Leica "M205C") at a dispersion state and magnification (approximately 500 to 1000 times) such that approximately 50 to 100 plate-like fillers were observed in the observation image. 1000 plate-like fillers were randomly selected using image analysis software (Mitani Shoji Co., Ltd. "WinROOF2015") to measure the major axis of the plate-like fillers, and the number average value was calculated, which was used as the average particle size of the plate-like fillers.
[0088] (7) Defects in molded products The liquid crystal polyester resin composition was dried at 150°C for 12 hours using a hot air dryer, and then subjected to a FANUC α30C injection molding machine (manufactured by FANUC). The cylinder temperature was set to the melting point of the liquid crystal polyester resin + 20°C, the mold temperature was set to 90°C, and the injection speed was set to 150 mm / s. The CPU sockets shown in Figs. 1 and 2 were injection molded by 100 shots. The 100 obtained CPU sockets were observed with an optical microscope, and the number of molded products with filling defects was counted. The fewer the number of filling defects, the fewer the defects and the better the product.
[0089] (8) Crack resistance The CPU socket injection molded in the same manner as in (7) was preheated for 2 minutes at a temperature of 200°C at 1.6°C / sec using a reflow simulator core9030c (manufactured by Cores Corporation), and reflowed for 30 seconds at a maximum surface temperature of 260°C. The socket was then cooled to room temperature and reflowed. The lattice part of the CPU socket after reflow processing was observed with an optical microscope to count the number of cracks. The fewer the number of cracks, the higher the crack resistance.
[0090] (9) Crack resistance during high-temperature, high-pressure molding A CPU socket was injection molded in the same manner as (7), except that the cylinder temperature was set to the melting point of the liquid crystal polyester resin + 40°C, the injection speed was set to 300 mm / s, and the molding pressure was increased. The number of cracks in the obtained CPU socket was measured in the same manner as (8). The fewer the number of cracks, the higher the crack resistance during high-temperature and high-pressure molding.
[0091] (10) Number of burrs on molded products The liquid crystal polyester resin composition was dried at 150°C for 12 hours using a hot air dryer, and then fed to a FANUC α30C injection molding machine (manufactured by FANUC) to injection mold 50 shots of the CPU socket shown in Fig. 1 and Fig. 2 under molding conditions of a cylinder temperature of the melting point of the liquid crystal polyester resin + 10°C, a mold temperature of 130°C, and an injection speed of 150 mm / s. This condition is more likely to cause burrs than the condition (7). The number of molded products with burrs and blocked pin insertion holes was counted for the 50 obtained CPU sockets, and the number of molded products with fewer burrs was considered to be superior.
[0092] [Table 2]
[0093] From the results in Table 2, it can be seen that the liquid crystal polyester resin composition containing a liquid crystal polyester resin (A) having a specific structural unit and a specific amount of inorganic filler has little outgassing during melt processing, so that even with a narrow pitch distance, there is little filling variation between molded products, and a CPU socket with few defects and burrs and excellent crack resistance can be obtained. Furthermore, it can be seen that when the inorganic filler contains a fibrous filler having a specific fiber length, a CPU socket with excellent crack resistance during high-temperature and high-pressure molding can be obtained. [Explanation of symbols]
[0094] 10 CPU sockets 1 Gate location 2 Outer frame 3 Lattice structure 4 Pin insertion hole 5 Opening [Industrial Applicability]
[0095] The CPU socket of the present invention has few defects and burrs even with a narrow pitch distance and has excellent crack resistance, making it particularly suitable for electrical and electronic component applications using such CPU sockets.
Claims
1. The CPU socket is formed from a liquid crystal polyester resin composition containing 60 to 200 parts by weight of an inorganic filler (B) per 100 parts by weight of a liquid crystal polyester resin (A) which is a liquid crystal polyester resin containing at least the following structural units (I) to (V) and which satisfies the following formulas (a) to (d): 25≦[I]≦75...(a) 1≦[II]≦20...(b) 2≦[III]+[IV]≦35...(c) 2≦[V]≦35...(d) ([I] to [V] indicate the content (mol %) of each of the following structural units (I) to (V) relative to 100 mol % of all structural units in the liquid crystal polyester resin.) 【Chemistry 1】
2. 2. The CPU socket according to claim 1, wherein said inorganic filler (B) contains at least a fibrous filler having an average fiber length of 1 to 300 μm, and the content of the fibrous filler is 65 to 100% by weight relative to 100% by weight of the inorganic filler (B).
3. 3. The CPU socket according to claim 2, wherein the fibrous filler has a fiber length of 100 [mu]m or more in an amount of 0.1% to less than 30% by number of fibers of the entire fibrous filler.
4. 2. The CPU socket according to claim 1, wherein said inorganic filler (B) contains at least a plate-like filler, and the content of the plate-like filler is 35% by weight or less relative to 100% by weight of said inorganic filler (B).
5. 2. The CPU socket according to claim 1, wherein the liquid crystal polyester resin (A) further contains the following structural unit (VI) and is a liquid crystal polyester resin that satisfies the following formula (e): 0.05≦[VI]≦10...(e) 【Chemistry 2】
6. 6. The CPU socket according to claim 1, wherein the minimum width of the resin portion of the lattice portion that constitutes the lattice structure is 0.2 mm or less.
Citation Information
Patent Citations
Liquid crystal polyester composition
JP2012193343A
Planar connector
JP2012214652A
Composite resin composition and flat connector molded from same
WO2014050370A1